Collective reflective learning for social justice in Nepal’s community-based natural resource management - Gurung, D. D.; Robertson, G.; Khadka, Manohara; Menon-Sen, K.; Staddon, S.; Barnes, C.; Saif, O. (University of Edinburgh, 2023)
This action research project brings together academics, experts in social inclusion and reflective learning, and practitioners working in Nepal’s community-based natural resources management (CBNRM) in order to recognise and critically reflect upon roots and processes of injustice as they operate within their own professional practice. We did so as the necessary first step to re-imagining gender equality and social inclusion in Nepal’s CBNRM and, in time, to transforming those injustices.